2018
DOI: 10.1152/japplphysiol.00158.2018
|View full text |Cite
|
Sign up to set email alerts
|

Thermosensory micromapping of warm and cold sensitivity across glabrous and hairy skin of male and female hands and feet

Abstract: The ability of hands and feet to convey skin thermal sensations is an important contributor to our experience of the surrounding world. Surprisingly, the detailed topographical distribution of warm and cold thermosensitivity across hands and feet has not been mapped, although sensitivity maps exist for touch and pain. Using a recently developed quantitative sensory test, we mapped warm and cold thermosensitivity of 103 skin sites over glabrous and hairy skin of hands and feet in male (M; 30.2 ± 5.8 yr) and fem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 70 publications
3
44
1
Order By: Relevance
“…); yet sex differences in thermal sensitivity are often ambiguous (Stevens & Choo, ), and so it remains to be fully clarified whether sex has an independent physiological role in those difference (Filingeri et al . ).…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…); yet sex differences in thermal sensitivity are often ambiguous (Stevens & Choo, ), and so it remains to be fully clarified whether sex has an independent physiological role in those difference (Filingeri et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…In this respect, we have recently shown that BSA‐size matched males and females present limited differences in warm and cold sensitivity across their hands and feet (Filingeri et al . ). It could be speculated that the greater female cold (and wetness) sensitivity observed here is driven by the fact that our female group had a smaller BSA than males (Table ) and that this translated in a greater proportion of their skin being stimulated by the fixed size (1.32 cm 2 ) thermal probe used (Table ).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations